Characterization of a multidrug resistant Citrobacter amalonaticus clinical isolate harboring blaNDM-1 and mcr-1.5 genes - Faccone, Diego Francisco (2019)
A multidrug resistant isolate, identified as Citrobacter amalonaticus using MALDI-TOF MS and confirmed by genomic analysis, was recovered from a pediatric patient in a hospital from Buenos Aires, Argentina. By whole-genome sequencing a total of 16 resistance genes were detected, including blaNDM-1 and mcr-1.5. To the best of our knowledge this is the first description of these two genes together in a clinical isolate of the Citrobacter genus.